Congenital Esophageal Cyst: about a case - Gallo, Enrique G; La Mura, Ricardo; Baldoni, Ruben D; Frank, Luis G (Cirugía del Uruguay, 1980)
Report of one case of congenital cyst in thorax pottion of esophagus. Review of etiopathogeny, diagnosis and therapy of this rare condition.